Tropaeolum tops tobacco - simple and efficient transgene expression in the order Brassicales. - Andrea Pitzschke (PLoS ONE)
Transient expression systems are valuable tools in molecular biology. Agrobacterial infiltration of leaves is well-established in tobacco, but has led to limited success in the model plant Arabidopsis thaliana. An efficient expression system combining the advantages of Arabidopsis (well-characterised) and the simplicity of leaf infiltration is desirable. Here, I describe Agrobacterium tumefaciens-mediated transformation of Tropaeolummajus (nasturtium, order Brassicales) as a remarkably simple, cheap and highly efficient transient expression system. It provides the Arabidopsis community with a tool to study subcellular localisation, protein-protein interactions and reporter gene activities (e.g. luciferase, β-glucuronidase) in a genetic background that is closely related to their primary model organism. Unlike Arabidopsis, Tropaeolum is capable of engaging in endomycorrhizal associations and is therefore relevant also to symbiosis research. RNAi-based approaches are more likely to succeed than in the distantly-related Nicotiana transformation system. Tropaeolummajus was voted the "medicinal plant of the year 2013". Conquering this plant for genetic manipulations harbours potential for biotechnological and pharmacological applications.